3(3+3d)=

Simple and best practice solution for 3(3+3d)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3+3d)= equation:


Simplifying
3(3 + 3d) = 0
(3 * 3 + 3d * 3) = 0
(9 + 9d) = 0

Solving
9 + 9d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 9d = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 9d = 0 + -9
9d = 0 + -9

Combine like terms: 0 + -9 = -9
9d = -9

Divide each side by '9'.
d = -1

Simplifying
d = -1

See similar equations:

| 3(4x+7)=-5 | | 25+k= | | 3+18y-1=9y+18-7y | | 1.1x=1.98 | | -3(-7x+3)+3x=2 | | 7y+2=8y-2y | | 6(-9+3x)=-108 | | 4x-10=2x+60 | | 0.25w=-2 | | 2x^2-2x=-14 | | 15-6x=2x-17 | | 10=9r+100 | | -6x^2+22x+8=0 | | -12-5n=-26 | | -4(6x+9)=204 | | -4x-12+6x-23=-2 | | 0.05-0.01(x+2)=-0.01(1-x) | | 10x-7-8x=-6 | | 8-3x=6-7x | | 5(2y-1)-2(2y)=-4 | | f(-2)=-3x+2 | | 7(3x+6)=147 | | 2x+6=1x-3 | | 27x^2=-66x+16 | | .2(x+3)-.4(2x-3)=3.4 | | -1+5x=x+35 | | -5(8x-2)+2x=3 | | 25=3z+(-10)-5+z | | x-(2x+5)=7 | | 12000(b+7)=408000 | | -18+12x=3(3x-2) | | -3x+7=7-6x |

Equations solver categories